KEUTAMAAN API SEBAGAI SIMBOL DEWA AGNI DALAM AKTIVITAS RITUAL KEAGAMAAN UMAT HINDU - Komang Heriyanti (Jnanasidanta, 2020)
Fire is an important element in human life. For Hindus people, fire has the main function in a religious ritual. Fire has a very deep theological meaning, because it is a symbol of God in its manifestation as an God Agni. Take fire material in empowering the universe, fire or Agni displayed in real during the ceremony by Hindus people. Various forms of fire in upakara facilities can be grouped into two, using Agni in the form of a flame and Agni in the form of fumes. Agni in the form of a flame like a torch. Agni in the form of fumes is certainly represented by incense and pasepan which prioritizes puffs of fumes in every religious ritual. This is seen in many daily rituals, both from canang and banten, which always use incense.Keywords: Fire, God Agni